Environmental contaminants and preeclampsia: a systematic literature review. (4th July 2018) - Rosen, Emma M.; Muñoz, MG Isabel; McElrath, Thomas; Cantonwine, David E.; Ferguson, Kelly K.
ABSTRACT: Preeclampsia is a medical condition specific to pregnancy characterized by high blood pressure and protein in the woman's urine, indicating kidney damage. It is one of the most serious reproductive conditions, posing substantial risks to the baby and potentially fatal for the mother. The causes of preeclampsia are largely unknown and environmental contaminants merit further investigation. The aim of this review was to determine the association between environmental chemical exposures and preeclampsia. PubMed was searched for articles examining a priori chemical exposures and preeclampsia through April 2018. Studies were included in our review if they included at least 10 cases, evaluated preeclampsia independent of gestational hypertension, and used either measured or modeled exposure assessments. Our review contained 28 investigations examining persistent organic pollutants (POP) (6 studies), drinking water contaminants (1 study), atmospheric pollutants (11 studies), metals and metalloids (6 studies), and other environmental contaminants (4 studies). There were an insufficient number of investigations on most chemicals to draw definitive conclusions, but strong evidence existed for an association between preeclampsia and cadmium (Cd). There is suggestive evidence for associations between nitrogen dioxide (NO2 ), particulate matter (PM)2.5, and traffic exposure with preeclampsia. There is evidence for an association between preeclampsia and Cd but insufficient literature to evaluate many other environmental chemicals. Additional studies using repeated measures, appropriate biological matrices, and mixtures methods are needed to expand this area of research and address the limitations of previous studies.